Three-Dimensional Facial Anthropometric Analysis With and Without Landmark Labelling: Is There a Real Difference?. Issue 2 (15th March 2022) - Gibelli, Daniele; Cappella, Annalisa; Bertozzi, Filippo; Sala, Davide; Sitta, Sara; Tasso, Damiano Rosario; Tomasi, Francesca; Dolci, Claudia; Sforza, Chiarella
Abstract : Introduction: The actual role of landmarks labeling before three-dimensional (3D) facial acquisition is still debated. In this study, several measurements were compared among textured labeled (TL), unlabeled (NL), and untextured (NTL) 3D facial models. Materials and Methods: The face of 50 subjects was acquired through stereophotogrammetry. Landmark coordinates were extracted from TL, NL, and NTL facial models, and 33 linear and angular measurements were calculated, together with surface area and volume. Accuracy of measurements among TL, NL, and NTL models was assessed through calculation of relative technical error of measurement (rTEM). The intra- and inter-observer errors for each type of facial model were calculated. Results: Intra- and inter-observer error of measurements increased passing from textured to NTL and NL 3D models. Average rTEMs between TL models, and NTL and NL models were 4.5 ± 2.6% and 4.7 ± 2.8%, respectively, almost all measurements being classified as "very good" or "good." Only for orbital height and its inclination, mandibular ramus length, nasal convexity, alar slope angle, and facial divergence, rTEM was classified as "moderate" or "poor." Conclusions: Accuracy and precision of measurements decrease when landmarks are not previously labeled; attention must be taken when measurements have a low magnitude or involve landmarks requiring palpation.